Advances in clinical chemistry. - Makowski, Gregory S. (Gregory Stephen) (ISSN, 2023)
Advances in Clinical Chemistry, Volume 115, the latest installment in this internationally acclaimed series, contains chapters authored by world-renowned clinical laboratory scientists, physicians and research scientists.